Mutations in the TolC Periplasmic Domain Affect Substrate Specificity of the AcrAB-TolC Pump - Marshall, Robert L.; Bavro, Vassiliy N. (Frontiers in Molecular Biosciences, 2020)
TolC and the other members of the outer membrane factor (OMF) family are outer membrane proteins forming trimeric channels that serve as a conduit for most actively effluxed substrates in Gram-negative bacteria by providing a key component in a multitude of tripartite efflux-pumps. Current models of tripartite pump assembly ascribe substrate selection to the inner-membrane transporter and periplasmic-adapter protein (PAP) assembly, suggesting that TolC is a passive, non-selective channel. While the membrane-embedded portion of the protein adopts a porin-like fold, the periplasmic domain of TolC presents a unique “alpha-barrel” architecture. This alpha-barrel consists of pseudo-continuous α-helices forming curved coiled-coils, whose tips form α-helical hairpins, relaxation of which results in a transition of TolC from a closed to an open-aperture state allowing effective efflux of substrates through its channel. Here, we analysed the effects of site-directed mutations targeting the alpha-barrel of TolC, of the principal tripartite efflux-pump Escherichia coli AcrAB-TolC, on the activity and specificity of efflux. Live-cell functional assays with these TolC mutants revealed that positions both at the periplasmic tip of, and partway up the TolC coiled-coil alpha-barrel domain are involved in determining the functionality of the complex. We report that mutations affecting the electrostatic properties of the channel, particularly the D371V mutation, significantly impact growth even in the absence of antibiotics, causing hyper-susceptibility to all tested efflux-substrates. These results suggest that inhibition of TolC functionality is less well-tolerated than deletion of tolC, and such inhibition may have an antibacterial effect. Significantly and unexpectedly, we identified antibiotic-specific phenotypes associated with novel TolC mutations, suggesting that substrate specificity may not be determined solely by the transporter protein or the PAP, but may reside at least partially with the TolC-channel. Furthermore, some of the effects of mutations are difficult to reconcile with the currently prevalent tip-to-tip model of PAP-TolC interaction due to their location higher-up on the TolC alpha-barrel relative to the proposed PAP-docking sites. Taken together our results suggest a possible new role for TolC in vetting of efflux substrates, alongside its established role in tripartite complex assembly.